The Oxford handbook of psychology and spirituality - Miller, Lisa J. (2022)
"A Spiritual Renaissance of Psychological Science has arrived: an explosion of rigorously derived, foundationally new models of human experience. In sum, the vision of psychological science in the Second Edition of the OUP Handbook of Psychology and Spirituality advances psychological research beyond twentieth century radical materialism and mechanism, to inform the rapidly evolving spiritually oriented global Zeitgeist that surrounds academia. In the First Edition of the OUP Handbook of Psychology and Spirituality leading researchers asserted a foundational new paradigm of spirituality and psychology, based upon an ontology that holds consciousness as primary, termed post-materialism. The most recent decade has spawned scholarly societies such as Academy for the Advancement of Post-Material Science and Open Sciences catalysing energetic collaboration, inquiry and discovery; engaging scientists to expand our understanding of the inherent spiritual nature of humanity and revolutionize our understanding of the human psyche. Studies reported in this volume, in design, data analysis and interpretation reveal a scientific migration from the conceiving of the "hermetic human," quite reflective of anthropocentric solipsism (as in 20th Century psychology), to a view of the "open-system human," ontologically existing as part of a surrounding field of consciousness, information, love and intention. Reported MRI studies in this volume explore consciousness not as epiphenomenal of the brain, nor as secondary to the foundational material brain, but as existing both independently and as existent broadly in and through mind, brain, human biology and all life. Some of the scholars in this volume show a radical shift for science in acknowledging a central "Source of consciousness," understood as a Higher Power, G-d, a generative intelligence in the universe. Known by many names to the world religious, wisdom and cultural traditions, here scientists observe a site line once found exclusively through religion through the lens of science. Post-materialism reorients clinical conceptualization, the goals and method of psychotherapy. In the Second Edition, several clinical scientists take spiritual awareness as core to mental health, whole person development and human biology. Psychological healing is part and parcel of spiritual growth and expanding human awareness. Absent in this volume is the vestige of monolithic pathologizing of transcendent perception and of suffering per se. Through this new lens, humans suffer when we limit our awareness, shut down perception of our connection with the fullness of existence. Naturally then we feel isolated, disempowered and the existential emptiness of being narrowly self-focused and generally self-serving. Depression and narcissism derive from our inherent telos to become more then a closed system, hermetic humans, from our starving to join the broader family of life. A form of depression, developmental depression, ignites and invites expansion of awareness. Treatment then moves from the narrow directive of mitigating symptoms and regaining functionality, to an opportunity for profound awakening to an alignment with the field of life. In a quest for augmenting spiritual awareness, clinical psychology moves from the post-industrial aim of "fix-it back to baseline" to a spiritual foundation for renewal. Now over two decades into the 21st century human psyche is seen as continuous with broader conscious field in and through nature, such that scientists meet here across so-called sub-disciplines of physics, biology, medicine and history. Science holds a mirror to longstanding spiritual truths held in religion and wisdom traditions"--
Revised edition of the author's The Oxford handbook of psychology and spirituality, c2012.
Includes bibliographical references and index.
Keywords: Psychology, Religious